A study on factors to the turnover at Tesco Kota Bharu / Haslinda Che Hassan - Che Hassan, Haslinda (Faculty of Business and Management, 2008)
This research was conducted to study the staff turnover toward Tesco Kota Bharu Kelantan. The objective of this research is to examine the factors to the staff turnover that can influence the company of Tesco Kota Bharu Kelantan. This study also was conducted to identify what are the most influencing factors for the staff turnover towards Tesco Kota Bharu Kelantan. Finally, the purpose of this study is also to recommend some idea and suggestion to solving the problems of the turnover toward Tesco Kota Bharu Kelantan. The researcher had using the secondary data that is from the previous report of the hypermarket staff turnover which weekly summary report of Tesco Kota Bharu Kelantan. Abscond, continue study, contract expired, healthy problems, terminate due to the disciplinary and getting the other jobs are the independent variables that being selected by the researcher. After collecting the data and analyze it, the result shows that the most factors that influence the staff turnover is abscond at Tesco Kota Bharu. The result also shows that healthy problems are not more influence to the staff turnover toward Tesco Kota Bharu. By conducting this research also, the researcher hopes that Human Resource Manager and the owner of Tesco Kota Bharu can reduced the staff turnover and improve the strategies of solving this problem of the Tesco Kota Bharu Kelantan.